Severe COVID-19 Illness: Risk Factors and Its Burden on Critical Care Resources - Yun, Kyongsik; Lee, Jeong Seok; Kim, Eun Young; Chandra, Himanshu; Oh, Baek-Lok; Oh, Jihoon (Frontiers in Medicine, 2020)
In South Korea, the first confirmed case of coronavirus 2019 (COVID-19) was detected on January 20, 2020. After a month, the number of confirmed cases surged as community transmission occurred, and the local hospitals experienced severe shortages in medical resources such as mechanical ventilators and extracorporeal membrane oxygenation (ECMO) equipment. With the medical claims data of 7,590 COVID-19 confirmed patients, this study examined how the claims for major medical resources and medications changed during the outbreak and stabilization period of COVID-19 in South Korea. We also aimed to investigate how the underlying diseases and demographic factors affect the disease severity. Our findings revealed that the risk of being treated with mechanical ventilator or ECMO (critical condition) was almost twice as high in men, and a previous history of hypertension, diabetes, and psychiatric diseases increased the risk for progressing to critical condition (Odds Ratio [95% CI], 1.60 [1.14-2.24]; 1.55 [1.55-2.06]; 1.73 [1.25-2.39], respectively). Chronic pulmonary disease did not significantly increase the risk for severity, but patients with a Charlson comorbidity index score of ≥5 and those treated in an outbreak area had an increased risk of developing critical condition (3.82 [3.82-8.15]; 1.59 [1.20-2.09], respectively). Our results may help clinicians predict the demand for medical resources during the spread of COVID-19 infection and identify patients who are likely to develop severe disease.